ASSESSMENT OF RISK AND PROTECTION IN NATIVE AMERICAN YOUTH: STEPS TOWARD CONDUCTING CULTURALLY RELEVANT, SUSTAINABLE PREVENTION IN INDIAN COUNTRY. Issue 3 (30th January 2017) - Guttmannova, Katarina; Wheeler, Melissa J.; Hill, Karl G.; Evans‐Campbell, Teresa A.; Hartigan, Lacey A.; Jones, Tiffany M.; Hawkins, J. David; Catalano, Richard F.
Abstract : This study constitutes a building block in the cultural adaptation of Communities That Care (CTC), a community‐based prevention system that has been found to be effective in reducing youth problem behaviors. Using the data from the CTC normative survey dataset that comprises more than a quarter million youth nationwide, this study examines the reliability and validity of scores derived from the CTC Youth Survey (CTC‐YS), one of the primary assessment tools for gathering community data on risk and protective factors related to problem behaviors including substance use. The reliability and criterion validity analyses are conducted overall for both the nationwide sample of youth and the student subsample of Native American youth. The results of this study indicate that the existing CTC‐YS assessments of risk and protective factors in the domains of community, family, school, and peer groups as well as within individuals yield scores that are reliable and valid within the Native American sample of youth. This study informs the third step in the CTC prevention planning process, which involves the assessment of risk and protective factors to be targeted in preventive interventions. The question of how the assessment of risk and protective factors among Native American youth might be further improved and a description of efforts related to the cultural adaptation of the CTC program currently underway also are addressed in the discussion.